EdTech and COVID-19 response [Save Our Future] - Haßler, Björn; Nicolai, Susan; McBurnie, Chris; Jordan, Katy; Wilson, Sam; Kreimeia, Adam (#SaveOurFuture, 2020)
This document is background paper 3 for the #SaveOurFuture campaign. The full paper and other working group papers are available here: https://saveourfuture.world/white-paper/. This document is also available as an EdTech Hub report, see https://docs.edtechhub.org/lib/IA9PL99D
Keywords: Author:Haßler; Author:OpenDevEd; AuthorFirst:Haßler; _EdTechHub_Output; _cover:v2; _r:ImportedToMyEducationEvidence; _yl:j; _yl:k; _zenodoODE; dode_eth-src-eth; dode_eth-trf2-dode